Reducing Anxiety among University Students in East Java Indonesia during Covid-19 Pandemic - Eka Sari, Jayanti Dian; Pratiwi, Xindy Imey; Wardani, Rifka Pramudia (Universitas Airlangga, 2024)
Background: Remote learning activities are one of the government's policies in the Covid-19 pandemic, which is still being implemented in the education sector. There were plenty of impacts that the students encountered, especially among college students who experienced difficulties in completing their final project to experienced anxiety. Aims: These conditions were the background in carrying out this study as it aimed to determine the efforts to reduce anxiety among final-year students. Methods: This was analytical observational research with a cross-sectional study design using the Theory of Planned Behaviour, undertaken across all cities and regencies in East Java from March to October 2021. The research population was all final-year college students with a sample of 385 respondents. Variables in this study were belief factors, intention, and behavior. Data collection was conducted by distributing online self-administered questionnaires. Data were presented statistically in tables and charts and analyzed using the non-parametric statistical test, multiple linear regression. Results: The result showed that the belief factor significantly influenced the intention variable (sig. 0.000), and the intention variable influenced final-year students' behavior in reducing anxiety (sig. 0.000). The intention variable had a significant value of 0.000 < 0.05, which indicated that the intention variable significantly influenced the final-year students' behavior to reduce anxiety. Based on the R square result, the intention variable influenced the final-year students' behaviour to reduce anxiety by 54%. Conclusion: Efforts known to reduce the anxiety of final-year students during the Covid-19 pandemic are managing stress, controlling themselves by increasing physical activity, doing hobbies, worship, positive thinking, and consuming the food they like.